Transmission Shaft Performance Using Static Simulation for Brushing Simulator - Tony, Jennevy; Md Salleh, Salihatun; Pauline, Ong; Yee, Low Cheng (Journal of Advanced Mechanical Engineering Applications, 2023)
The brushing simulator assists researchers and dentists in conducting investigations on human teeth and plaque removal. In this paper, the development of a brushing simulator is studied. Which focuses on the life expectancy of shaft material used in the development process in the future. The aim of this study is to analyse the stress distribution of the aluminium and brushing simulator’s stainless steel threaded shafts. Besides, to analyse the brushing simulator’s threaded shaft life expectancy. The motor speed of Set 1 can be modified to 450 rpm, 480 rpm, 510 rpm, or 540 rpm. Meanwhile, speeds for set 2 are 550 rpm, 580 rpm, 610 rpm, and 640 rpm. In this study, Solidworks software was used to construct a brushing simulator model and obtain the result of stress distribution in a static simulation. The life expectancy of the aluminium and stainless-steel threaded shafts was determined from the design calculation method by using the simulation data. The threaded shaft life expectancy result showed that stainless steel is more durable than aluminium which is 3522 hours from set 1 compared to 728 hours at 640 rpm for the aluminium threaded shaft. Based on its material properties, the findings indicate that stainless steel is stronger than aluminium. Furthermore, the study shows that life expectancy at speeds below 550 rpm is higher than at speeds above 550 rpm. Hence, the life expectancy of a threaded shaft decreases as the speed increases.